Relationship between symptoms during a gastric emptying study, daily symptoms and quality of life in patients with diabetes mellitus. Issue 12 (8th April 2021) - Kuwelker, Saatchi; Prichard, David O.; Bailey, Kent; Bharucha, Adil E.
Abstract: Aims: Gastric emptying is of limited utility for predicting the severity of symptoms in patients with diabetes mellitus and gastrointestinal symptoms. We evaluated the extent to which symptoms recorded during a 13 C‐spirulina‐based gastric emptying breath test (GEBT) or scintigraphy predicting the severity of daily symptoms in diabetes mellitus. Methods: Gastric emptying, symptoms during a gastric emptying study, either scintigraphy (n = 38) or GEBT (n = 111), and daily gastrointestinal symptoms were evaluated in 149 patients with diabetes mellitus and variably severe gastrointestinal symptoms. Key Results: Gastric emptying was normal, delayed, and rapid in 37%, 52%, and 9% measured with the GEBT and 55%, 34%, and 11% of patients measured with scintigraphy; differences between GEBT and scintigraphy were not significant. Daily symptoms were moderately severe or more intense in 58% and 21% of patients undergoing scintigraphy and GEBT ( P  < 0.0001). Symptoms during the GEBT (46%) and emptying thalf (3%) explained 50% of the variance in daily symptoms in the GEBT group. In the scintigraphy group, symptoms explained 29% of this variance; the thalf was insignificant. Patients who reported that one or more symptoms were more severe than the others during the GE study were more likely (OR 3.98, 95% CI 2.16, 7.33) to report the same symptom(s) as being the most severe in the daily diary. Conclusions: Symptoms during a GEBT and to a lesser extent during scintigraphy, but not gastric emptying predict the severity of daily symptoms and may serve as a biomarker in patients with diabetes mellitus.